DEVELOPMENT OF SCRAPOPBOX (SCRAP AND POP-UP BOX) ANIMAL METAMORPHOSIS IN ELEMENTARY SCHOOLS - Dian Ma'rifatus Sholikhah; Nataria Wahyuning Subayani; Nanang Khoirul Umam (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
In learning science in elementary schools, there are still many misconceptions, especially about animal metamorphosis material. Based on this then conducted research That aims To develop learning media Scrapopbox animal metamorphosis material. The process of developing learning media uses the development model that has been developed by Reiser and Mollenda, the ADDIE model with five stages, namely analysis, planning, development, implementation, and evaluation. The results of the development are in the form of Scrapopbox learning media in which there are scrap, pop-ups, and miniature toy animals. This study involved 18 grade V students. The data collection used was the validation of learning media, THB, and response questionnaires. With data analysis, namely analysis of validity, analysis of effectiveness, and analysis of user responses. Based on the analysis of data validation results, trials and user responses of Scrapopbox media, animal metamorphosis material meets the good criteria. The results of learning media validation by two media expert validators obtained a percentage of 87.5% which was categorized as valid and could be used during the learning process. It is categorized as effective from the results of THB, the results of the percentage of classical learning completeness are 100%, then the students' learning completeness is achieved because it reaches a score of ≥ 75%, for the results of students' responses to Scrapopbox media reaching a percentage of 98.33 % which is categorized as very good.